Parallel lightweight Block Cipher algorithm for Multicore CPUs - Hawraa J. Hamiza; Ahmed Fanfakh (مجلة بغداد للعلوم)
Data protection has become one of the top issues despite major advancements in communications and technology. For web-based technology to send data quickly and safely, the data must be encrypted. Encryption is the process of turning plain text into ciphred text, which bad people can't read or change. Both the cryptanalysis and decryption procedures required a large amount of time in order to maintain the requisite level of security. However, a number of researchers developed the cryptography approach in parallel in order to reduce the amount of time needed for the encryption and decryption procedures to be finished. The investigation of the issue has produced a number of viable solutions. Researchers were able to attain improved performance levels on the encryption technique by using parallelism to increase the throughput and boost the efficiency of encryption methods. To achieve high performance, lightweight speck cipher algorithms have been presented and implemented on CPU platforms with various improvements. Thus, in this work, a lightweight cipher scheme is proposed which only employs one round of block cipher technique that is applied in parallel over a multicore processor. The proposed message encryption algorithm uses two subblocks of 128 bits of plain message and substitution box and splitmix64 PRNG to encrypt the plain message and obtain two encrypted subblocks, making it a fast technique to encrypt and decrypt blocks of messages. In comparison to the existing method. According to the performance findings, it is able to reach a high data throughput in comparison to some lightweight methods that already exist, with a throughput that is higher than 25 Gigabits per second on an Intel Core i7 central processing unit. The proposed encryption method outperforms the parallel speck method by an average of 14.10 times faster when executed over a multicore CPU. The average speedup compared to the sequential version of the proposed algorithm and its parallel implementation is 4.70. Also, the proposed encryption method offers a substantial amount of randomness and passes PractRand's statistical tests. Thus, the suggested method is a strong contender for high-security implementation on multicore processors.